POLICY BRIEF Konseling Perubahan Perilaku bagi Pelaku Kekerasan dalam Rumah Tangga dalam Sistem Peradilan Pidana - Saeroni; Triantono (MAQASHID Jurnal Hukum Islam, 2021)
This policy brief was prepared based on the results of research conducted on “Pyco-legal Aspects in Taking Action against Perpetrators of Domestic Violence in DI. Yogyakarta." This research is intended to answer, "the extent to which the opportunities for applying psycho-legal aspects through additional criminal mechanisms of behavior change counseling for perpetrators of domestic violence in the criminal justice system." based on experience in the Special Region of Yogyakarta. This research is a normative-empirical legal research type with a focus on seeing the extent of behavioral change counseling opportunities for perpetrators of domestic violence in the criminal justice system. Data collection was carried out by means of a literature review, and analysis of 65 Decisions on Domestic Violence Cases in District Courts throughout DIY in 2005-2019. Data collection was also carried out through focus group discussions (Focus Group Discussion) with legal assistants, psychological assistants, service agencies, the Police, the Prosecutor's Office, District Courts, Ministry of Law and Human Rights, legal practitioners, as well as in-depth interviews (in-depth interviews), with male counselors, and male perpetrators of domestic violence, as well as experts.